Archaeological Survey of Dynamic Coastal Landscapes and Paleoshorelines: Locating Early Holocene Sites in the Prince Rupert Harbour Area, British Columbia, Canada. (3rd April 2018) - Letham, Bryn; Martindale, Andrew; Waber, Nicholas; Ames, Kenneth M.
ABSTRACT: We present and test a predictive archaeological survey model that targets early Holocene paleoshorelines in the Prince Rupert Harbour area using LiDAR bare earth digital terrain models and a 15, 000-year reconstructed history of relative sea level change. Despite a century of archaeological research in the study area, no sites dating earlier than 6000cal b.p. had been identified prior to our research. Our field survey identified three early Holocene sites associated with paleoshorelines 7–10 m above current sea level (masl). These locations demonstrate repeated use through the Holocene even as shoreline position changes. We discuss these new data in relation to the early Holocene archaeological record from the rest of the northern Northwest Coast and suggest that the region was ubiquitously occupied by this time and that the lack of recorded early Holocene sites in some areas is likely a result of survey and preservation bias, rather than historical reality.